1+MG Coordination Group - Kok, Ruben (2021)
The “1+ Million Genomes” (1+MG) initiative is a cooperation mechanism involving by now 24 countries and was launched on Digital Day 2018. Countries meet on a regular basis in order to make sure that the aim of the 1+MG Declaration - to have at least 1 million sequenced genomes accessible in the EU by 2022 - is achieved. Genomics has the potential to revolutionise healthcare in many ways. It could lead to the development of more targeted personalised medicines, therapies and interventions. It could also enable better diagnostics, boost prevention and make more efficient use of scarce resources. From cancer, to rare diseases, neuro diseases and prevention, genomics can greatly improve health conditions of EU citizens. Equally important, genomics has the potential to improve the effectiveness, accessibility, sustainability and resilience of health systems in the European Union